CHILDHOOD AND EDUCATION: HORIZONS OF HISTORICAL RESEARCH IN LATIN AMERICA - Kuhlmann Junior, Moysés; Campos Alba, Elida Lucila (Historia y Memoria de la Educación, 2024)
This article delves into the historiography of childhood and its education in Latin America from 1990 to 2020. The sources under consideration are the works of literature, articles, and communications presented at the 14 meetings of the Ibero-American Congresse on the History of Education, structured around three axes: historiography and childhood, politics and institutions, and society and culture. Referred to historiography, after an overview of the framework that propelled childhood research from the 1990s, the article engages in a discussion on the configuration of the field and the criteria employed in organizing the texts. In the second axis, it explores the theme of early childhood education examining it through four subcategories: pedagogy, policies, educational institutions, and biographies. In the analysis of the society and culture, the article brings to light the discernible differences marking social inequalities. Several issues stand out, including the necessity to consider the age range employed in research, the imbalance in childhood studies among Latin American countries, and the limited number of studies on children under three years old. In conclusion, the article underscores the imperative for research on the topic to consider the political, cultural, and social structures of each period. It advocates for regional and international comparative studies on childhood education, encompassing both formal and informal aspects. Furthermore, the article highlights the importance of exploring teacher training, the education of girls and boys, and providing a platform for the voices of children to understand the ways of appropriation and resistance across different generations.